(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Infectious diseases pose a significant burden to bangladesh. Water borne diarrhoeal diseases and respiratory tract infections are most prevalent due to poor quality of life as well as due to poor educational status. Tuberculosis and malaria are common and leishmaniasis is endemic in some part of the country. Besides owing to epidemic shift for rapid urbanization non-communicable diseases like cancer, diabetes mellitus, ischaemic heart disease and stroke are also responsible for significant burden to bangladesh. Some of the infectious diseases has emerged and reemerged in the recent past. The zoonotic diseases like avian influenza a/h5n1, nipah virus, japanese encephalitis virus, rabies and other communicable diseases like salmonella, hepatitis e virus, rotavirus sometimes cause outbreak in certain parts. Most of these diseases are preventable. This review will discuss the super imposed burden of non-communicable disease over emerging and re-emerging infectious diseases of public health importance in bangladesh and the underlying causes of less progress to improve detection and control. JCMCTA 2015 ; 26 (2) : 9 - 16